Christopraxis : A Practical Theology of the Cross - Root, Andrew, 1974- (Book collections on Project MUSE., 2014)
Since the late 1970's practical theology has had a significant voice and influence in the academy. While many have seen great hope and potential in this work, not everyone has agreed. Some, for instance, have examined the conversation and found by focusing on the concrete and lived experiences of humanity, by and large, practical theology has not had the theological vision to present frameworks for understanding concrete and lived experience with divine action. So argues Andrew Root, who in Christopraxis seeks to reset the entire edifice of practical theology on a new foundation. While not minimizing practical theology's commitment to the lived and concrete, Root argues that practical theology has neglected deeper theological underpinnings, and seeks to create a practical theology that seeks to be fully post-postmodern, post-Aristotelian, and that in seeking to attend to doctrines such as divine action and justification, is properly and fully theological.